Bio-socio-cultural factors affecting the nutritional status among pre-schoolers of Mamanua conquista tribe in Barangay Cantugas, Mainit, Surigao Del Norte - Sario, Imelda G. Sabandal (1999)
This study focused on the assessment of the bio-socio-cultural factors associated with the nutritional status of the 95 Mamanua Conquista preschool children in Barangay Cantugas, Mainit, Surigao Del Norte in May 1996. It described the dietary intake and feeding practices of 0-6 year old children and determined the prevalence of malnutrition. The relationships of bio-socio-cultural factors to the nutritional status of the children were likewise evaluated. The nutritional status was ascertained using weight-for-age, height-for-age, weight-for-height, and middle-upper-arm circumference (MUAC). Dietary intake was recorded for three days, i.e., two-week days and one on weekend using a modified 24-hour recall method.Results of this study indicated that 17.0and 2.0of the children were moderately and severely underweight for their age, respectively. About half of the preschoolers (49.5were mildly underweight-for-age. Stunting affected 13.7of the children, while 2.1suffered from severe chronic form of malnutrition, found mostly among the one and three years of age.The diet of children from the family pot consisted mainly of rice porridge or "lugao" with small amount of fish and salt. The children's diet when compared with the Recommended Dietary Allowances (RDA) provided 52.6adequacy for energy and 66.8adequacy for protein (31.1animal protein and 69.0vegetable protein). All other essential nutrients likewise fell short of the RDA.Multiple regression analysis was applied to identify important bio-socio-cultural factors associated with the nutritional status of the Mamanue Conquista children. Significant association was observed between weight-for-age and percent adequacy of energy, duration of breastfeeding and priority given to food distribution. Weight-for-height on the other hand, was significantly associated with age of the child, number of meals served, source of water supply, and household income. The adequacy of protein and energy intake, duration of breastfeeding and age were found to have significant associations with height-for-age. The MUAC was associated with income.Planners and nutritionists can utilized the results of the study in the development of nutritious and inexpensive menus for preschoolers, based on locally available foods and other nutrition intervention programs in consonance with the culture and tradition of the Mamanua Conquista community. Likewise, the Agricultural Training Institute (ATI) with other local government units can help increase subsitence farming production through provision of seedlings for homeyard/community gardening and through seminars on farming technology. Moreover, results can be utilized by different government and non-governmental agencies in planning nutrition and economic programs to improve the bio-social and food security status of this tribal group.